2020
DOI: 10.1016/j.neuropsychologia.2020.107574
|View full text |Cite
|
Sign up to set email alerts
|

Children with dyslexia utilize both top-down and bottom-up networks equally in contextual and isolated word reading

Abstract: Introduction:Executive functions (EF) include cognitive processes that support learning and reading. Children with dyslexia experience challenges with both reading and reading comprehension. The neurobiological support for EF deficits during reading comprehension, however, has yet to be defined. Here we aimed to identify the neural networks related to EF during a reading comprehension task focusing on top-down and bottom-up networks in children with dyslexia and typical readers (TR).Method: Twenty children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 57 publications
1
5
0
Order By: Relevance
“…In line with this view, a prior study has demonstrated that the DMN is involved in visualmotor learning (Eryurek et al, 2022). On the other hand, the VAN is an attentional control network that serves the processing of unexpected stimuli, reflecting the bottom-up control processing, consistent with previous findings of the dysfunction of ventral and dorsal attentional networks in dyslexics (Meri et al, 2020). Previous studies have also found that the VAN was positively correlated with DMN during childhood (Barber et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…In line with this view, a prior study has demonstrated that the DMN is involved in visualmotor learning (Eryurek et al, 2022). On the other hand, the VAN is an attentional control network that serves the processing of unexpected stimuli, reflecting the bottom-up control processing, consistent with previous findings of the dysfunction of ventral and dorsal attentional networks in dyslexics (Meri et al, 2020). Previous studies have also found that the VAN was positively correlated with DMN during childhood (Barber et al, 2013).…”
Section: Discussionsupporting
confidence: 82%
“…Moreover, reading ability may rely on the balanced integration of top-down and bottom-up processing. In comparison to typical readers, individuals with DD showed reduced functional connectivity between the neural substrates of top-down and bottom-up processing [ 97 ] and reduced activation of frontal and parietal cortical areas associated with the attentional control network during reading tasks [ 98 ]. Likewise, individuals with comorbid reading disability and ADHD have shown specific deficits in frontal regions within the frontal-striatal pathway [ 48 ], which has been functionally related to impairments in executive functioning [ 47 , 49 ], an ability central to the attentional control network.…”
Section: Discussionmentioning
confidence: 99%
“…It might be that for these readers, word reading level is relatively automatic and therefore does not demand the recruitment of EFs. However, the utilization of EF and reading-related neural circuits might be needed for contextual reading and reading comprehension ( Meri et al, 2020 ). This was also observed in Meri et al (2020) in an fMRI-based study focusing on reading comprehension and EF networks in TRs and children with RDs.…”
Section: Discussionmentioning
confidence: 99%